Ответы и объяснения

Лучший Ответ!
2013-07-14T21:38:36+04:00

 

(2x-7)/(x^2 + 2x - 8)  - 1 => 0

2x - 7 - x^2 - 2x + 8 => 0

-x^2 + 1 => 0

x1 = +1

x2 = -1

 

x^2 + 2x - 8 > 0

(x +4)(x-2)>0

x=-4

x=2

 

x=(-беск. ; -4) U [-1; 1] U (2 ; +беск)

2013-07-14T22:19:28+04:00

Знаменатель сторого > 0.

 x2 + 2x - 8 > 0
корни: (x +4)(x-2)>0
x1=-4 x2=2  

 

 Приравниваем к нулю::

((2x-7) / (x2 + 2x - 8)) - 1= 0
2x - 7 - x2 - 2x + 8 => 0
-x2 + 1 = 0
x1 = 1 x2 = -1
Ответ:
x=(-\infty ; -4) U {-1; 1} U (2 ; + \infty )